Proposing a New Managerial Model for Digital Transformation - Tayazime, Jihane; Moutahaddib, Aziz (European Scientific Journal, ESJ, 2022)
Digital transformation is a gateway to innovation and new models of organization, operations, and business models. The quick response of managers and leaders is becoming the key to successful digital transformation, followed by strategic flexibility according to data testing results. These results highlight the importance of agile leadership in today’s changing organizational environment (Fachrunnisa et al., (2020). Hence why it is imperative to take into consideration all employees’ perceptions of management to avoid resistance to change. Thus, in this research paper, we analyze the current managerial environment to better guide digital transformation through a survey destined for both managers and employees, assessing the current situation of organizational management from a diversity of perspectives. We then propose a new digital transformation managerial model based on significant correlations between the models’ variables using the Chi-squared test.